2010
DOI: 10.1038/nature08895
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomic screen for modulators of ciliogenesis and cilium length

Abstract: Primary cilia are evolutionarily conserved cellular organelles that organize diverse signaling pathways1,2. Defects in the formation or function of primary cilia are associated with a spectrum of human diseases and developmental abnormalities3. Genetic screens in model organisms have discovered core machineries of cilium assembly and maintenance4. However, regulatory molecules that coordinate the biogenesis of primary cilia with other cellular processes, including cytoskeletal organization, vesicle trafficking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
612
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(674 citation statements)
references
References 24 publications
39
612
1
3
Order By: Relevance
“…It is likely that a variety of pathways contribute to modifications of cilia length and structure. 16,22 Cyclic loading of the rat tail tendons in the current study was able to maintain cilia length (with respect to fresh controls) in tendons loaded immediately following harvest and reverse (shorten) cilia lengthened in response to SD, returning them to control lengths. Previous studies from our lab have shown that the loading scheme utilized in the current study (3% strain at 0.17 Hz) were able to maintain tendon cell homeostasis with respect to catabolic gene expression 27 or decrease catabolic gene expression in 24 h SD tendons.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is likely that a variety of pathways contribute to modifications of cilia length and structure. 16,22 Cyclic loading of the rat tail tendons in the current study was able to maintain cilia length (with respect to fresh controls) in tendons loaded immediately following harvest and reverse (shorten) cilia lengthened in response to SD, returning them to control lengths. Previous studies from our lab have shown that the loading scheme utilized in the current study (3% strain at 0.17 Hz) were able to maintain tendon cell homeostasis with respect to catabolic gene expression 27 or decrease catabolic gene expression in 24 h SD tendons.…”
Section: Discussionmentioning
confidence: 96%
“…Cilia lengthening has been observed in response to loss of fluid flow in kidney epithelial cells 31,32,18 and cytoskeletal disruption in human embryonic kidney cells. 22 Previous studies from our lab have shown that fluid flow in tendons occurs in response to tensile loading 25,27 and SD of tendon cells results in an immediate disruption of the actin cytoskeleton in these cells. 23 While the presence or absence of physical signals appears to be related to changes in cilia length, the precise mechanism(s) and pathways involved in mediating these changes are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Consistent with these observations, nucleating factors that promote actin polymerization repress primary cilium assembly and growth whereas actin severing enzymes promote ciliogenesis. [14][15][16][17] Actin depolymerization promotes ciliogenesis by stabilizing the pericentrosomal preciliary compartment, a vesiculotubular structure that contributes to ciliogenesis, 14,15,17 and by inhibiting transcription factors from the Hippo pathway, which induce the expression of cilium disassembly factors. 17 The small GTPase RhoA plays a key role in actin network regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Pitaval and colleagues (2010) found that actin cytoskeleton function was required for the response of cilia to the stretched area, which is consistent with the idea that actin is an integrator of global cellular mechanics. Actin has been implicated in ciliogenesis in large-scale screens (Kim et al 2010) although the mechanistic role of actin in ciliogenesis remains completely unknown.…”
Section: Mechanical Forces Affect Ciliogenesismentioning
confidence: 99%